Adnexal Torsion with Dystrophic Calcifications in an Adolescent: A Chronic Entity? - Pinar Solmaz Hasdemir; Fatma Eskicioglu; Gokhan Pekindil; Ali Riza Kandiloglu; Tevfik Guvenal (Case Reports in Obstetrics and Gynecology)
Intermittent pelvic pain caused by ovarian cysts in adolescence may be due to torsion or partial torsion of the ovary. We present a case of 18-year old adolescent with symptomatic left ovarian torsion with calcifications demonstrated by pelvic MRI and ultrasonography prior to surgery. The pathologic investigation demonstrated dystrophic calcifications. We speculated that the pattern of the intermittent pain in the story of the patient and the dystrophic calcifications in pathologic investigation which is thought that it might have been potentially developed as a result of chronic hypoxia due to intermittent partial torsions over a period of two years.